2013
DOI: 10.1089/gtmb.2012.0302
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 Polymorphisms and Systemic Lupus Erythematosus: A Comprehensive Meta-Analysis

Abstract: Objective: The aim of this study was to determine whether the SNPs + 49A/G and CT60A/G of the CTLA-4 gene are associated with susceptibility to systemic lupus erythematosus (SLE). Methods: The comprehensive metaanalysis for + 49A/G included 1753 cases and 2279 controls, and for CT60A/G included 676 cases and 576 controls. Allelic and genotypic comparisons between cases and controls were evaluated. For + 49A/G, we also subdivided it by population. Results: For + 49A/G, statistically significant differences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
(46 reference statements)
0
7
0
1
Order By: Relevance
“…This SNP was shown to play an important role in T and B cell receptor signaling (5). The SNP rs3087243 in CTLA4 is associated with several autoimmune diseases, including SLE, RA, T1D, and Graves' disease (8,(10)(11)(12)(13)(14). The CTLA4 SNP has a protective effect, and the major allele G is associated with autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…This SNP was shown to play an important role in T and B cell receptor signaling (5). The SNP rs3087243 in CTLA4 is associated with several autoimmune diseases, including SLE, RA, T1D, and Graves' disease (8,(10)(11)(12)(13)(14). The CTLA4 SNP has a protective effect, and the major allele G is associated with autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…However, its precise mechanism of action has not been fully resolved. Recently abnormal CTLA-4 gene polymorphisms and function has been reported in SLE patients (52,53). For the first time to our knowledge, in this system we found that B cells and granulocytes also can be "tolerized" and subsequently function as regulatory/suppressor cells to prevent production of autoantibodies.…”
Section: Discussionmentioning
confidence: 55%
“…However, its precise mechanism of action has not been fully resolved. Recently abnormal CTLA-4 gene polymorphisms and function has been reported in SLE patients ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, they may alter the transcription capacity of the CD152 gene [ 18 ], the processing and transport of CD152 protein [ 19 ], and the interactions between CD152 and CD80 ligand [ 20 ]. Therefore, they have been widely explored their influences on autoimmune disorders [ 21 ] and cancer [ 22 ].…”
Section: Introductionmentioning
confidence: 99%